Evidences on central venous catheter-associated sepsis (Research, Society and Development, 2023)
This study aims to identify the predisposing factors for sepsis associated with the Central Venous Catheter. Based on the above, carrying out the same is justified by its academic, scientific and social relevance, having as its agenda, evaluating the evidence regarding CVC-associated sepsis, highlighting the recommendations and protocols to minimize the incidence rates of related infections to this procedure. Thus, the methodology used is an integrative review where a survey of data was carried out in the scientific bases: PubMed, BVS Brasil, LILACS and SCIELO. Results showed that high ICU mortality is usually associated with sepsis due to mishandling of invasive devices such as CVCs, which must be maintained and implanted for a specific period of time to prevent infections. The prolonged use of the device is pointed out by the Ministry of Health as one of the main risk factors for the occurrence of infections. Thus, the use of antiseptic techniques and a trained team is essential to avoid contamination. Improper handling of the CVC can result in a serious complication that can lead to patient mortality. Considering the facts above, the importance of qualifying the care team can be seen. It is important to pursue strategies for training in proper device use over the long term to ensure device monitoring and hygiene to prevent infection.